How do French patients perceive the environmental impact of drugs? - Cherif, Sirajdine; Michel, Bruno (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Medications account for nearly one-third of healthcare-related greenhouse gas emissions in France, yet their environmental impact remains largely overlooked in public discourse. This study aimed to explore how patients with chronic illnesses perceive their medications’ ecological footprint and identify opportunities for a more sustainable pharmaceutical model supported by patient engagement. An anonymous survey was conducted via an online survey among French adults with chronic illnesses (asthma, diabetes, multiple sclerosis, rheumatoid arthritis, and chronic myeloid leukaemia) to explore their awareness and attitudes regarding the environmental impact of medications. The 11-item questionnaire was distributed via patient associations and social media over two weeks (October 15–November 1, 2024). Data were analysed using descriptive and comparative statistics; open-ended responses were thematically explored. Nearly 90.0% (n=202) of respondents were willing to choose medications with a lower environmental impact, provided their efficacy and tolerability were equivalent. However, 47.0% (n=104) of patients were unsure if there is a link between environmental impact and medication effectiveness, highlighting a significant lack of clarity on the topic. This uncertainty reinforces the need for accessible and transparent information. Over 88.0% (n=199) of participants wished to be informed about the environmental footprint of their treatments, favouring labelling on medication packaging. While most patients were willing to act individually—by returning unused medications or choosing greener options—only 68.7% (n=155) reported using recycling programs, a rate below the national documented average of 81.0%. Patients also expressed a strong desire for systemic change: 87.0% (n=195) supported the inclusion of environmental criteria in national medication evaluation policies, and they also expected the pharmaceutical industry to invest in sustainability, while remaining cautious about potential economic trade-offs. In conclusion, patients are open to contributing to a more sustainable healthcare model, but a lack of clear, trustworthy information and accessible environmental options hinders their willingness. Public institutions, healthcare providers, and pharmaceutical companies must work together to support this shift by raising awareness and making sustainable choices visible, credible, and actionable within the patient care pathway.